2019
DOI: 10.4018/978-1-5225-7817-8.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Management and Corporate Governance in Family Firms

Abstract: Earnings management and corporate governance relationships are examined for a sample of 49 Portuguese listed firms considering an unbalanced panel for the period 2002-2017, using panel corrected standard errors models and considering the family ownership effect. Empirical findings reveal that there is a positive relationship between corporate board independence and earnings management and that the presence of women on board decreases earnings management practices. Results are consistent with the hypothesis tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…According to H2b, we find a weakly significant association between the interaction “women on the board-RPTs and downward AEM”. Like previous literature, we find that the presence of women on the board, per se , exerts a lowering effect on the propensity to manipulate earnings using discretionary accrual (Vieira and Madaleno, 2019). On the other hand, our results suggest that when family firms' management engages in high levels of RPTs, extracting resources from the company, gender diversity tends to produce an opposite effect and might enhance the level of downward EM in order to reduce the exit of resources from the company via dividends or taxation.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…According to H2b, we find a weakly significant association between the interaction “women on the board-RPTs and downward AEM”. Like previous literature, we find that the presence of women on the board, per se , exerts a lowering effect on the propensity to manipulate earnings using discretionary accrual (Vieira and Madaleno, 2019). On the other hand, our results suggest that when family firms' management engages in high levels of RPTs, extracting resources from the company, gender diversity tends to produce an opposite effect and might enhance the level of downward EM in order to reduce the exit of resources from the company via dividends or taxation.…”
Section: Resultssupporting
confidence: 80%
“…The literature has investigated the influence of women directorship on EM in family firms. Findings point out that the presence of women on a board decreases EM (Vieira and Madaleno, 2019; Mnif and Cherif, 2020), although a previous study carried out in Malaysia showed that family ownership does not interact with women on boards to influence the propensity for EM (Abdullah and Ismail, 2016).…”
Section: Theoretical Framework Literature Review and Hypotheses Devel...mentioning
confidence: 63%
See 3 more Smart Citations